2007
DOI: 10.1097/01.wnp.0000236606.53923.0d
|View full text |Cite
|
Sign up to set email alerts
|

Motor Unit Action Potential Duration, I: Variability of Manual and Automatic Measurements

Abstract: The aim of this work is to analyze the variability in manual measurements of motor unit action potential (MUAP) duration and to evaluate the effectiveness of well-known algorithms for automatic measurement. Two electromyographists carried out three independent duration measurements of a set of 240 MUAPs. The intraexaminer and interexaminer variabilities were analyzed by means of the Gage Reproducibility and Repeatability method. The mean of the three closest manually marked positions was considered the gold st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Algorithms used to automatically measure MUP duration are based on amplitude and slope criteria, but because of variable amounts of background noise, the algorithms have low stability and visual inspection and manual marker adjustments are often required (Bischoff et al, 1994;Stalberg et al, 1995;Takehara et al, 2004b). Previous studies have shown low reliability in manual placement of duration markers and therefore manual corrections do not guarantee reliable estimates of MUP duration (Chu et al, 2003;Nandedkar et al, 1988;Rodriguez et al, 2007;Stalberg et al, 1986;Takehara et al, 2004a). In a study conducted by Rodriquez et al (Rodriguez et al, 2007) where the variability between two experienced electromyographers in manual measurements of MUP duration using four automated methods was examined, significant differences within electromyographers and between electromyographers were found in the tibialis anterior (TA) muscle but not in the FDI.…”
Section: Mup Durationmentioning
confidence: 95%
“…Algorithms used to automatically measure MUP duration are based on amplitude and slope criteria, but because of variable amounts of background noise, the algorithms have low stability and visual inspection and manual marker adjustments are often required (Bischoff et al, 1994;Stalberg et al, 1995;Takehara et al, 2004b). Previous studies have shown low reliability in manual placement of duration markers and therefore manual corrections do not guarantee reliable estimates of MUP duration (Chu et al, 2003;Nandedkar et al, 1988;Rodriguez et al, 2007;Stalberg et al, 1986;Takehara et al, 2004a). In a study conducted by Rodriquez et al (Rodriguez et al, 2007) where the variability between two experienced electromyographers in manual measurements of MUP duration using four automated methods was examined, significant differences within electromyographers and between electromyographers were found in the tibialis anterior (TA) muscle but not in the FDI.…”
Section: Mup Durationmentioning
confidence: 95%
“…The accuracy of CAMs has been systematically assessed in normal and pathological MUAPs [42] [45]. Comparing the GSPs (determined by means of the probabilistic method referred above) with the marker positions obtained with CAMs ( Figure 9), mean differences of up to 8.5 ms were found, with the T1 CAM.…”
Section: Accuracy Of Conventional Automatic Methodsmentioning
confidence: 99%
“…In another study, for a systematic quantitative estimation of the intra-and inter-examiner variability in MUAP duration measurements, the Gage Reproducibility and Repeatability (Gage R&R) method [40,41] was applied [42]. This method is based on the analysis of the variance of repeated measurements of a given feature, and it is currently applied in industrial quality control studies.…”
Section: Variability Of Manual Measurementsmentioning
confidence: 99%
See 2 more Smart Citations